Autonomic Dysfunction in Preschool Children with Neurotic Disorders - Olexyuk, Zaryana; Konkabayeva, Aiman; Alshynbekova, Gulnaziya; Tykezhanova, Gulmira; Nugumanova, Sholpan; Mukasheva, Manara (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
In the last decades of the 21st century, the problem of a significant increase in the number of children with disorders in mental and somatic development has become particularly acute. Often there are neurotic conditions caused by the influence of various psycho-traumatic factors: the growth of scientific and technological progress and related changes in all areas of human life activity. In this regard, shifts occurred in the structure of the incidence among the population towards an increase in the proportion of diseases associated with nervous and psychic overstrain. One of the most vulnerable age groups is children of preschool and primary school age. Untimely diagnosed neurotic disorders in children, as a rule, turn into protracted forms of neurotic conditions and subsequently become chronic. This, of course, affects the adaptation of the individual in society and the further quality of life. This study, aimed at assessing autonomic regulation in preschool children with different psychological status, allowed to reveal the activity of the sympathetic and parasympathetic link of the autonomic nervous system (ANS) by the method of cardiointervalography according to R.M. Baevskii. We examined 127 children aged 4-5.5 years old. The average statistical indicators characterizing the regulation of heart rate (HR, HF, LF, VLF, LF/HF, TP, SI) in preschool children in various groups (neurosis, pre-neurosis, anxiety, and normal) were determined. The study revealed changes in the regulation of heart rhythm in children with neurotic disorders, which indicates an increase in the influence of the sympathetic circuit of autonomic regulation and a decrease in parasympathetic influences. Overstrain of vegetative centres in children with neurosis and pre-neurotic conditions is determined by high psychoemotional stresses.